Perovskite oxide thin film using selective A-site atomic gradient and preparation method thereof
By introducing A-site atomic layer gradient structure into perovskite oxide films, the limitations of strong polarity and polarity functions in the prior art are solved, and strong polarization and improvement without the help of special substrates or devices are achieved Dielectric and thermoelectric characteristics.
Patent Information
- Application Number
- CN202410744632.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-06-15
- Filing Date
- 2024-06-11
- Publication Date
- 2024-12-17
AI Technical Summary
The prior art has limitations in inducing strong polarity and polarity functions, especially in substrates, physical properties and equipment. The flexural electric effect method is accompanied by crystallization point defects, and the composition gradient method is used in the verification of strong polarity and functionalities. limited.
Using a perovskite oxide film, by introducing a gradient structure into its A-site atomic layer, the layered structure of the chemical formula A1-xA'xBO3, A and A' are different divalent or trivalent cations, and B is tetravalent Or trivalent cations form thin films through physical vapor deposition and other methods to achieve the deflection symmetry without the help of a special oxygen pattern substrate or device.
A universal inversion symmetry failure in the material is achieved, resulting in large electropolarization and improved dielectric properties and thermoelectric effects, and no special substrate or device support is required, and the polarization amplitude and thermoelectric coefficient are significantly improved.
Smart Images

Figure CN119143171A_ABST
Abstract
Description
[0001] This application claims priority to and the benefit of Korean Patent Application No. 10-2023-0076849 filed in the Korean Intellectual Property Office on June 15, 2023, the entire contents of which are incorporated herein by reference. Technical Field
[0002] This research was carried out with the support of Samsung Research Funding & Incubation Center for Future Technology (Project No. SRFC-MA2101-02).
[0003] This research involves perovskite oxide thin films using selective A-site atomic gradients and methods for their preparation, and involves a general method that can generate large electric polarization and realize polar functions in perovskite oxide ABO3. Background Art
[0004] Traditionally, the following methods are usually used to artificially break inversion symmetry or generate polarization inside the material.
[0005] One example is a method for controlling the oxygen octahedral rotation pattern. In this method, when the oxygen octahedral rotation pattern (e.g., a - b + a - ) in a material with a polar symmetric pattern (e.g., a - a - a - ) substrate, the material follows the same pattern as the substrate to achieve polar symmetry.
[0006] When having a - a - a - The patterned LaAlO3 is grown on a Glazer labeled a - b + a - When the oxygen octahedral rotation pattern of the non-polar CaTiO3 material is used, the non-polar CaTiO3 material shows polarity and has the same a - a - a - pattern.
[0007] Another example is the Schottky junction method. The Schottky junction method refers to the case where a metal material is joined to a semiconductor material. This method realizes polar characteristics through a built-in field caused by band bending that occurs in the process of adjusting different Fermi levels. For example, if a built-in field is generated by joining a semiconductor of niobium (Nb)-doped SrTiO3 or TiO2 to gold, piezoelectric effect and thermoelectric effect may occur.
[0008] In addition, another example may be the flexoelectric effect. This method utilizes the phenomenon that electric polarization occurs in all materials due to strain gradient, that is, the flexoelectric effect. Although the piezoelectric effect is limited only in 20 crystal point groups, the flexoelectric effect can advantageously occur in all 32 point groups. In addition, because the strain gradient is inversely proportional to the length unit, the flexoelectric effect that works more significantly at the nanometer unit and the electric polarization that occurs through the flexoelectric effect can be used differently at the nanometer level.
[0009] In addition, yet another example may be a conventional composition gradient method, which is a method of inducing a composition gradient in the thickness direction by changing the composition ratio of two different composition atoms and artificially destroying the inversion symmetry. This method is generally used for metal alloys, etc., but has recently been used for some oxides. This method has the advantage of artificially / universally destroying the inversion symmetry through various material combinations.
[0010] However, the Schottky junction method or the oxygen octahedron rotation pattern control method has limitations of working at the junction of a metal and a semiconductor and using only a substrate having a polar structure, respectively.
[0011] Furthermore, currently known methods of exploiting the flexoelectric effect caused by strain gradients have the limitation of being inevitably accompanied by many crystallographic point defects and only work when used with other devices such as scanning probe microscopes.
[0012] Furthermore, previously studied composition gradient methods have not been experimentally validated in terms of the strong polarity (electric polarization) and polar functionality that can be artificially produced by them, and have limitations in terms of the magnitude of the polarity (electric polarization) and the functionality that can be achieved.
[0013] Therefore, it is necessary to verify a method and functionality that can universally induce strong polarity (electric polarization) without being limited by substrates, physical properties, or devices.
[0014] [Prior art]
[0015] [Non-patent references]
[0016] 1. Kim, J. R., Jang, J., Go, K. J. et al. Stabilizing hidden room-temperature ferroelectricity via a metastable atomic distortion pattern. Nat Commun 11, 4944 (2020).
[0017] 2. Yang, M. M., Luo, Z. D., Mi, Z. et al. Piezoelectric and pyroelectric effects induced by interface polar symmetry. Nature 584, 377–381 (2020).
[0018] 3. D. Lee, A. Yoon, S. Y. Jang, J.-G. Yoon, J.-S. Chung, M. Kim, J. F. Scott, T. W. Noh. Giant flexoelectric effect in ferroelectric epitaxial thin films. Phys. Rev. Lett. 107, 057602 (2011).
[0019] 4. Wu, P. C., Huang, R., Hsieh, Y. H. et al. Electrical polarization induced by atomically engineered compositional gradient in complex oxide solid-solution. NPG Asia Mater 11, 17 (2019).
[0020] 5. Damodaran, A., Pandya, S., Qi, Y. et al. Large polarization gradients and temperature-stable responses in compositionally-graded ferroelectrics. Nat Commun 8, 14961 (2017). Summary of the Invention
[0021] One aspect of the present disclosure provides a perovskite oxide film that can universally produce inversion symmetry breaking within the material without using a substrate with a special oxygen pattern or without the assistance of other devices, and can form polarization through the flexoelectric effect, and can achieve improved dielectric properties and thermoelectric effects.
[0022] According to one aspect, a perovskite oxide thin film includes a compound represented by Chemical Formula 1 and has a layered perovskite structure, wherein a ratio of A' atoms in one A site atomic layer to all A sites is different from a ratio of A' atoms in three or more other A site atomic layers to all A sites in a thickness direction.
[0023] [Chemical formula 1]
[0024] A 1-x A' x BO3
[0025] In Chemical Formula 1, A and A′ are different divalent or trivalent cations, B is a tetravalent or trivalent cation, and 0≤x≤1.
[0026] A and A' may each independently include strontium (Sr), calcium (Ca), barium (Ba), lanthanum (La), cerium (Ce), praseodymium (Pr), neodymium (Nd), promethium (Pm), samarium (Sm), europium (Eu), gadolinium (Gd), terbium (Tb), dysprosium (Dy), holmium (Ho), erbium (Er), thulium (Tm), ytterbium (Yb), lutetium (Lu) or a combination thereof.
[0027] B may include titanium (Ti), vanadium (V), chromium (Cr), manganese (Mn), iron (Fe), cobalt (Co), nickel (Ni), copper (Cu), zinc (Zn), or a combination thereof.
[0028] The one A-site atomic layer may be a first atomic layer, which is an A-site atomic layer located on the inner side in the thickness direction of the perovskite oxide thin film.
[0029] The three or more different A-site atomic layers may be: a second atomic layer, which is an A-site atomic layer located on one surface of the perovskite oxide film; a third atomic layer, which is an A-site atomic layer located on another surface of the perovskite oxide film; and a fourth atomic layer, which is an A-site atomic layer located on the inner side in the thickness direction of the perovskite oxide film and different from the first atomic layer.
[0030] The ratio of A' atoms to all A sites in the first atomic layer and the fourth atomic layer (R 1 ) can each independently be greater than 0 and less than about 1.
[0031] The ratio (R 2 ) of the A' atoms in the second atomic layer to all A sites can be greater than or equal to 0 and less than about 1.
[0032] The ratio (R 3 ) of the A' atoms in the third atomic layer to all A sites can be greater than about 0 and less than or equal to about 1.
[0033] The first atomic layer can be the A-site atomic layer of a compound represented by Chemical Formula 1.
[0034] The second atomic layer can be the A-site atomic layer of a compound represented by Chemical Formula 2.
[0035] [Chemical Formula 2]
[0036] ABO3
[0037] In Chemical Formula 2, A is a divalent or trivalent cation different from A', and B is a tetravalent or trivalent cation.
[0038] The third atomic layer can be the A-site atomic layer of a compound represented by Chemical Formula 3.
[0039] [Chemical Formula 3]
[0040] A'BO3
[0041] In Chemical Formula 3, A' is a divalent or trivalent cation different from A, and B is a tetravalent or trivalent cation.
[0042] The fourth atomic layer can be the A-site atomic layer of a compound represented by Chemical Formula 4.
[0043] [Chemical Formula 4]
[0044] A 1-z A' z BO3
[0045] In Chemical Formula 4, A and A' are different divalent or trivalent cations, B is a tetravalent or trivalent cation, 0 < z < 1, and z ≠ x.
[0046] The compound represented by Chemical Formula 1 can be Ba 1-x Ca x TiO3, the compound represented by Chemical Formula 2 can be BaTiO3, the compound represented by Chemical Formula 3 can be CaTiO3, and the compound represented by Chemical Formula 4 can be Ba 1- z Ca z TiO3.
[0047] The perovskite oxide thin film may have a thickness-direction gradient in which a ratio of A′ atoms in one A-site atomic layer to all A sites varies in the thickness direction.
[0048] The perovskite oxide thin film may have a thickness direction gradient calculated by Formula 1 of 0.5% to 50%.
[0049] [Formula 1]
[0050] △G(%)=(AL n+1 -AL n )×100
[0051] In Formula 1, ΔG is the gradient in the thickness direction, AL n is the ratio of A' atoms in any A-site atomic layer to all A-sites, and AL n+1 is the ratio of A' atoms in other A-site atomic layers with spacing less than or equal to about 0.4 nm to all A-sites.
[0052] The total thickness of the perovskite oxide thin film may be about 1.2 nm to about 100 nm.
[0053] An atomic ratio of A atoms to A′ atoms in the entire perovskite oxide thin film may be about 30:70 to about 70:30.
[0054] The average magnitude of the polarization induced throughout the perovskite oxide film may be greater than or equal to about 20 μC / cm 2 .
[0055] The dielectric loss of the entire perovskite oxide thin film may be less than or equal to about 0.1 under measurement conditions of a frequency of 1 kHz to 2 MHz and an AC level of 10 mV to 200 mV.
[0056] Under the measurement conditions of a sinusoidal temperature change period of 20 seconds to 120 seconds and a low frequency period (LFP) of a temperature change of 0.5K to 8K, the thermoelectric coefficient of the entire perovskite oxide film can be greater than or equal to about 10 5 μC / m 2 K.
[0057] According to another aspect, a method for preparing a perovskite oxide thin film includes: forming a perovskite oxide thin film on a substrate, wherein the perovskite oxide thin film includes a compound represented by Chemical Formula 1 and has a layered perovskite structure, wherein a ratio of A' atoms in one A site atomic layer to all A sites is different from a ratio of A' atoms in three or more other A site atomic layers to all A sites in a thickness direction.
[0058] [Chemical formula 1]
[0059] A 1-x A' x BO3
[0060] In Chemical Formula 1, A and A′ are different divalent or trivalent cations, B is a tetravalent or trivalent cation, and 0≤x≤1.
[0061] The perovskite oxide thin film may be formed by physical vapor deposition (PVD), chemical vapor deposition (CVD), molecular beam epitaxy (MBE), atomic layer deposition (ALD), or pulsed laser deposition (PLD).
[0062] The perovskite oxide thin film may be formed using a PLD (pulsed laser deposition) apparatus equipped with a high-pressure and high-speed reflection electron diffraction device (reflection high-energy electron diffraction) under specific conditions of a rate of 2 pulses / unit cell to 200 pulses / unit cell.
[0063] According to an embodiment, a perovskite oxide thin film can generally generate inversion symmetry breaking within the material and form polarization through the flexoelectric effect without using a substrate with a special oxygen pattern or without the assistance of other devices, has improved dielectric properties, and can generate a thermoelectric effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0064] Figure 1 is a diagram schematically illustrating a perovskite oxide thin film according to an embodiment.
[0065] Figure 2 The RHEED intensity oscillation used to form the A-site atomic layer gradient when a perovskite oxide film having an A-site atomic layer gradient is prepared using a high-pressure and high-speed reflection electron diffraction device (reflection high energy electron diffraction, RHEED) is shown.
[0066] Figure 3 The solid solution Ba prepared in the comparative example is shown. 0.5 Ca 0.5 Aberration-corrected scanning transmission electron microscopy (STEM) measurements of TiO3 thin films.
[0067] Figure 4 The aberration-corrected scanning transmission electron microscopy (STEM) measurement results of the (Ba,Ca)TiO3 thin film with A-site atomic layer gradient prepared in Example are shown.
[0068] Figure 5 The solid solution Ba prepared in the comparative example is shown. 0.5 Ca 0.5 Results of atomic-level chemical mapping of TiO3 thin films using energy dispersive X-ray spectroscopy (EDS).
[0069] Figure 6 The results of atomic-level chemical mapping using energy dispersive X-ray spectroscopy (EDS) of a (Ba,Ca)TiO3 thin film with an A-site atomic layer gradient prepared in Example are shown.
[0070] Figure 7 and Figure 8 Shown are the corresponding Figure 5 and Figure 6 Polarization diagram.
[0071] Fig. 9 The solid solution Ba prepared in the comparative example is shown. 0.5 Ca 0.5 Graph of the frequency-dependent dielectric constant of the (Ba,Ca)TiO3 film with A-site atomic layer gradient prepared in TiO3 films, etc. and Examples.
[0072] Fig.10 The solid solution Ba prepared in the comparative example is shown. 0.5 Ca 0.5 Graph showing the tan δ characteristics of the (Ba,Ca)TiO3 thin film with A-site atomic layer gradient prepared in TiO3 thin films, etc. and Examples.
[0073] Fig.11 The (Ba, Ca) TiO3 film with the A-site atomic layer gradient prepared in the example and the (Ca, Ba) TiO3 film with the atomic layer gradient in the opposite direction and the solid solution Ba prepared in the comparative example are shown. 0.5 Ca 0.5 Graph showing the thermoelectric properties of TiO3 thin films. DETAILED DESCRIPTION
[0074] Hereinafter, various embodiments of the present invention will be described in detail with reference to the accompanying drawings so that those skilled in the art can easily implement the present invention. The present invention can be implemented in many different forms and is not limited to the embodiments described herein.
[0075] In order to clearly explain the present invention, parts irrelevant to the description are omitted, and the same or similar components are given the same reference numerals throughout the specification.
[0076] In addition, unless explicitly described to the contrary, the word “comprise” and variations such as “including” or “having”, will be understood to imply the inclusion of stated elements but not the exclusion of any other elements.
[0077] Will refer to Figure 1 A perovskite oxide thin film 100 according to an embodiment is described. Figure 1 is a diagram schematically showing a perovskite oxide thin film 100 according to an embodiment.
[0078] Reference Figure 1 , the perovskite oxide thin film 100 according to the embodiment includes the compound represented by Chemical Formula 1.
[0079] [Chemical formula 1]
[0080] A 1-x A' x BO3
[0081] In Chemical Formula 1, A and A' are different divalent or trivalent cations, B is a tetravalent or trivalent cation, and 0≤x≤1. In this case, B may be a cation different from A and A'.
[0082] For example, in Chemical Formula 1, A and A' may each independently include: an alkaline earth metal such as strontium (Sr), calcium (Ca) or barium (Ba); a rare earth metal such as lanthanum (La), cerium (Ce), praseodymium (Pr), neodymium (Nd), promethium (Pm), samarium (Sm), europium (Eu), gadolinium (Gd), terbium (Tb), dysprosium (Dy), holmium (Ho), erbium (Er), thulium (Tm), ytterbium (Yb) or lutetium (Lu); or a combination thereof. Here, A and A' may be different from each other, and for example, A may be barium (Ba) and A' may be calcium (Ca).
[0083] B may be a transition metal including titanium (Ti), vanadium (V), chromium (Cr), manganese (Mn), iron (Fe), cobalt (Co), nickel (Ni), copper (Cu), zinc (Zn), or a combination thereof.
[0084] x represents the atomic percentage of A' atoms, and may be 0≤x≤1.
[0085] The perovskite oxide thin film 100 has a layered perovskite structure.
[0086] For example, in a layered perovskite structure, A atoms or A' atoms are located between BO6 octahedra that share each edge in three dimensions. For reference, Figure 1 The two-dimensional structure of the layered perovskite is shown, and the BO6 octahedron is shown as a square.
[0087] The layered perovskite structure includes multiple A-site atomic layers between BO6 octahedra in the thickness direction, and the multiple A-site atomic layers include A atoms, A' atoms, or both A atoms and A' atoms. In addition, the A-site atomic layers may include additional oxygen atoms because they share oxygen atoms with the BO6 octahedra.
[0088] Here, the ratio of A' atoms in one A site atomic layer to all A sites may be different from the ratio of A' atoms in three or more other A site atomic layers to all A sites in the thickness direction. Here, the thickness direction may be a direction perpendicular to a substrate (not shown) or a direction parallel to the growth direction of the perovskite oxide thin film 100. The perovskite oxide thin film may be a thin film grown in the 001 plane direction, a thin film grown in the 110 plane direction, or a thin film grown in the 111 plane direction. Hereinafter, the thin film grown in the 001 plane direction will be mainly described, but is not limited thereto.
[0089] As an example, one A-site atomic layer may be an A-site atomic layer located on the inner side in the thickness direction of the perovskite oxide thin film 100 (hereinafter, referred to as “first atomic layer AL1”). Three or more other A-site atomic layers may respectively include an A-site atomic layer located on one surface of the perovskite oxide thin film 100 (hereinafter, referred to as “second atomic layer AL2”), an A-site atomic layer located on the other surface of the perovskite oxide thin film 100 (hereinafter, referred to as “third atomic layer AL3”), and an A-site atomic layer located on the inner side in the thickness direction of the perovskite oxide thin film 100 and different from the first atomic layer (hereinafter, referred to as “fourth atomic layer AL4”).
[0090] That is, the second atomic layer AL2 and the third atomic layer AL3 may be located on one surface and the other surface in the thickness direction of the perovskite oxide thin film 100 , respectively, and the first atomic layer AL1 and the fourth atomic layer AL4 may be located between the second atomic layer AL2 and the third atomic layer AL3 .
[0091] For example, the first atomic layer AL1 may be an A-site atomic layer of the compound represented by Chemical Formula 1. Here, the ratio (R 1 ) may be greater than about 0 and less than about 1, for example, greater than or equal to about 0.14 and less than about 1, greater than or equal to about 0.28 and less than about 1, greater than or equal to about 0.58 and less than about 1, greater than or equal to about 0.72 and less than about 1, greater than or equal to about 0.86 and less than about 1, greater than about 0 and less than or equal to about 0.14, greater than about 0 and less than or equal to about 0.28, greater than about 0 and less than or equal to about 0.58, greater than about 0 and less than or equal to about 0.72, or greater than about 0 and less than or equal to about 0.86. As an example, the compound represented by Chemical Formula 1 included in the first atomic layer AL1 may be Ba 1-x Ca x TiO3.
[0092] In the second atomic layer AL2, the ratio of A' atoms to all A sites (R 2) can be greater than or equal to about 0 and less than about 1, for example, greater than or equal to about 0.14 and less than about 1, greater than or equal to about 0.28 and less than about 1, greater than or equal to about 0.58 and less than about 1, greater than or equal to about 0.72 and less than about 1, or greater than or equal to about 0.86 and less than about 1.
[0093] The second atomic layer AL2 can be the A-site atomic layer of the compound represented by Chemical Formula 2.
[0094] [Chemical Formula 2]
[0095] ABO3
[0096] In Chemical Formula 2, A is a divalent or trivalent cation different from A', and B is a tetravalent or trivalent cation. For example, the compound represented by Chemical Formula 2 can be BaTiO3.
[0097] In the third atomic layer AL3, the ratio (R) of A' atoms to all A sites 3 ) can be greater than about 0 and less than or equal to about 1, for example, greater than about 0 and less than or equal to about 0.14, greater than about 0 and less than or equal to about 0.28, greater than about 0 and less than or equal to about 0.58, greater than about 0 and less than or equal to about 0.72, or greater than about 0 and less than or equal to about 0.86.
[0098] The third atomic layer AL3 can be the A-site atomic layer of the compound represented by Chemical Formula 3.
[0099] [Chemical Formula 3]
[0100] A'BO3
[0101] In Chemical Formula 3, A' is a divalent or trivalent cation different from A, and B is a tetravalent or trivalent cation. For example, the compound represented by Chemical Formula 3 can be CaTiO3.
[0102] The fourth atomic layer AL4 can be the A-site atomic layer of the compound represented by Chemical Formula 4.
[0103] [Chemical Formula 4]
[0104] A 1-z A' z BO3
[0105] In Chemical Formula 4, A and A' are different divalent or trivalent cations, B is a tetravalent or trivalent cation, 0 < z < 1, and z ≠ x.
[0106] Here, in the fourth atomic layer AL4, the ratio (R) of A' atoms to all A sites 1) may be greater than about 0 and less than about 1, for example, greater than or equal to about 0.14 and less than about 1, greater than or equal to about 0.28 and less than about 1, greater than or equal to about 0.58 and less than about 1, greater than or equal to about 0.72 and less than about 1, greater than or equal to about 0.86 and less than about 1, greater than about 0 and less than or equal to about 0.14, greater than about 0 and less than or equal to about 0.28, greater than about 0 and less than or equal to about 0.58, greater than about 0 and less than or equal to about 0.72, or greater than about 0 and less than or equal to about 0.86. As an example, the compound represented by Chemical Formula 4 included in the fourth atomic layer AL4 may be Ba 1-z Ca z TiO3, wherein z is different from x in Chemical Formula 1.
[0107] In this way, the ratio of A' atoms to all A sites in one A site atomic layer (first atomic layer AL1) is different from the ratio of A' atoms to all A sites in three or more other A site atomic layers (second atomic layer AL2, third atomic layer AL3 and fourth atomic layer AL4) in the thickness direction.
[0108] In addition, the first atomic layer AL1 and the fourth atomic layer AL4 may be the nearest A-site atomic layers adjacent to each other. That is, the perovskite oxide thin film 100 may have different ratios of A′ atoms to all A sites in units of A-site atomic layers.
[0109] As an example, the perovskite oxide thin film 100 may have a thickness-direction gradient in which the ratio of A′ atoms in one A-site atomic layer to all A sites varies in the thickness direction.
[0110] For example, the ratio of A' atoms to all A sites of the first atomic layer AL1 may decrease stepwise or gradually as approaching the second atomic layer AL2, and the ratio of A' atoms to all A sites of the first atomic layer AL1 may increase stepwise or gradually as approaching the third atomic layer AL3.
[0111] That is, the thickness direction gradient calculated by Formula 1 may be about 0.5% to about 50%, or about 2% to about 20%.
[0112] [Formula 1]
[0113] △G(%)=(AL n+1 -AL n )×100
[0114] In formula 1, △G is the gradient in the thickness direction, AL n is the ratio of A' atoms in any A-site atomic layer to all A-sites, and AL n+1is the ratio of A' atoms in other A-site atomic layers with spacing less than or equal to about 0.4 nm to all A-sites. For example, AL n can be the ratio of A' atoms in the first atomic layer AL1 to all A sites, and AL n+1 It can be the ratio of A' atoms to all A sites in the fourth atomic layer AL4.
[0115] As an example, Figure 1 The case where 7 layers of perovskite crystal structure are stacked is shown. Therefore, it includes 8 layers of A-site atomic layers, and the ratio of A' atoms in each A-site atomic layer to all A sites has the following gradient in the thickness direction: the ratio of A' atoms changes stepwise or gradually in the thickness direction. For reference, in Figure 1 The difference in the ratio of the A' atom to all A sites is represented by the shaded ratio within the atom.
[0116] For example, in the second atomic layer AL2, the shadow of the A' atom is 0%, indicating that the atomic ratio of A atoms to A' atoms (A:A') is 1.00:0.00, in the third atomic layer AL3, the shadow of the A' atom is 100%, indicating that the atomic ratio of A atoms to A' atoms (A:A') is 0.00:1.00, in the first atomic layer AL1, the shadow of the A' atom is 58%, indicating that the atomic ratio of A atoms to A' atoms (A:A') is 0.42:0.58, and in the fourth atomic layer AL4, the shadow of the A' atom is 42%, indicating that the atomic ratio of A atoms to A' atoms (A:A') is 0.58:0.42.
[0117] In this way, the perovskite oxide thin film 100 selectively and precisely controls the ratio of A atoms and A′ atoms having different ionic radius sizes in each A-site atomic layer, thereby generating a very large strain gradient in nanometer thickness.
[0118] Therefore, the inversion symmetry inside the material can be universally broken, and polarization can be formed by the flexoelectric effect without using a substrate with a special oxygen pattern or without the help of other devices. For example, when Ba with an ionic radius of 0.161 nm is used at the A site in the titanate film of ATiO3, 2+ ions and Ca with an ionic radius of 0.131 nm 2+ When using ions to make an atomic gradient film with a thickness of about 3nm, the lattice gradient is about 10 8 / m, and considering that the general flexoelectric coefficient is 10 -9 C / m to 10 -8 C / m, can generate about 10μC / cm 2 to about 100μC / cm 2This method is generally applicable regardless of the ion at the B position that determines the physical property and can therefore be used to combine various physical properties and polar structures.
[0119] As an example, the total thickness of the perovskite oxide thin film 100 may be about 1.2 nm to about 100 nm, for example, about 2.4 nm to about 20 nm, or about 4.3 nm to about 10 nm. That is, when the ratio of A' atoms in the A site atomic layer to all A sites is changed in units of A site atomic layers, the perovskite oxide thin film 100 according to the embodiment can induce strong and stable electric polarization even in an ultra-thin film of about 4 nm.
[0120] The atomic ratio of A atoms to A' atoms in the entire perovskite oxide film 100 may be about 30:70 to about 70:30, for example, about 40:60 to about 60:40, or about 50:50. For example, CaTiO3 is a non-polar material without polarization, and BaTiO3 has a carbon content of less than or equal to about 20 μC / cm at a film thickness. 2 In which CaTiO3 and BaTiO3 are uniformly mixed and the Ba:Ca ratio is 50:50 (Ba 0.5 Ca 0.5 ) In the case of the TiO3 solid solution film, there is no polarization. On the other hand, in the case of the perovskite oxide film 100 according to the embodiment, when the ratio of the A' atom in the A site atomic layer to all the A sites is changed in units of the A site atomic layer, the flexoelectric effect can be exhibited even when the atomic ratio of the A atoms to the A' atoms in the entire perovskite oxide film 100 is 50:50.
[0121] Therefore, the average magnitude of the polarization induced in the entire perovskite oxide thin film 100 may be greater than or equal to about 20 μC / cm 2 , for example, greater than or equal to about 30 μC / cm 2 , or greater than or equal to about 50 μC / cm 2 , and the maximum magnitude of the polarization induced in the entire perovskite oxide thin film 100 may be greater than or equal to about 60 μC / cm 2 , greater than or equal to about 70μC / cm 2 , or greater than or equal to about 100 μC / cm 2 .
[0122] Because polarization is formed during film synthesis at high temperature, when the perovskite oxide thin film 100 according to the embodiment is a thin film at high temperature, as the ratio of A' atoms in the A site atomic layer to all A sites changes in units of A site atomic layers, charged defects (e.g., oxygen vacancies) move toward the interface, resulting in a very clean defect-free state inside the film. In addition, since the perovskite oxide thin film 100 has a large polarization gradient, a bulk bound charge density (bulk bound charge density, ) having a large negative value is caused. ), so that electrons, which are the main external carriers in the oxide, are depleted inside the film. As a result, the dielectric properties of the perovskite oxide thin film 100 are improved even in a very thin and ultra-thin film.
[0123] Therefore, under the measurement conditions of a frequency of 1 kHz to 2 MHz and an AC (alternating current) level of 10 mV to 200 mV, the dielectric loss of the entire perovskite oxide thin film 100 is less than or equal to about 0.1, for example, less than or equal to about 0.01, or less than or equal to about 0.001. On the other hand, in a thin film having a thickness of about 5 nm manufactured using a conventional method, the leakage current is very large due to trapped charges, making it impossible to measure dielectric and function-related results.
[0124] In addition, since the perovskite oxide thin film 100 according to the embodiment inevitably has a region where a paraelectric-ferroelectric phase transition occurs inside the film within the temperature range for measuring thermoelectricity, the dielectric constant, the flexoelectric coupling coefficient, and the flexoelectric coefficient proportional to the product of these two values can change rapidly within the measurement temperature range, and the change of the flexoelectric coefficient in response to the temperature change can diverge. As a result, the perovskite oxide thin film 100 has an ultra-large thermoelectric property even if it is a very thin and ultra-thin film.
[0125] Therefore, under the measurement conditions of a low frequency period (LFP) with a sinusoidal temperature variation period of 20 seconds to 120 seconds and a temperature variation period of 0.5K to 8K, the thermoelectric coefficient of the entire perovskite oxide thin film 100 may be greater than or equal to about 10 5 μC / m 2 K, for example, is greater than or equal to about 10 6 μC / m 2 K, or greater than or equal to about 10 7 μC / m 2 K. On the other hand, in a thin film with a thickness of about 5 nm produced by a conventional method, trapped charges generate a current out of phase with the thermoelectric current, making it impossible to measure thermoelectricity and function-related results.
[0126] A method for preparing a perovskite oxide thin film according to an embodiment may include: forming a perovskite oxide thin film on a substrate, the perovskite oxide thin film including a compound represented by Chemical Formula 1 and having a layered perovskite structure, wherein a ratio of A' atoms in one A site atomic layer to all A sites is different from a ratio of A' atoms in three or more other A site atomic layers to all A sites in a thickness direction.
[0127] [Chemical formula 1]
[0128] A 1-x A' x BO3
[0129] In Chemical Formula 1, A and A′ are different divalent or trivalent cations, B is a tetravalent or trivalent cation, and 0≤x≤1.
[0130] The perovskite oxide thin film 100 according to an embodiment may be formed by a physical vapor deposition (PVD) method (eg, a sputtering method), a chemical vapor deposition (CVD) method, a molecular beam epitaxy (MBE) method, an atomic layer deposition (ALD) method, or a pulsed laser deposition (PLD) method.
[0131] As an example, the perovskite oxide thin film 100 may be formed by using a pulsed laser deposition (PLD) apparatus equipped with a high pressure-high energy reflection electron diffraction device under the conditions of 2 pulses / unit cell to 200 pulses / unit cell, or under the conditions of 50 pulses / unit cell or more.
[0132] When a PLD (pulsed laser deposition) device equipped with a high-pressure high-energy reflection electron diffraction device is used, by using only a first target material including A atoms and a second target material including A' atoms, materials with many different composition ratios (A atoms: A' atoms) can be controlled at a single atomic layer level. That is, it is not necessary to use N targets to manufacture N layers of thin films as in the prior art.
[0133] Hereinafter, specific examples of the present invention are given. However, the examples described below are only used to illustrate or explain the present invention in detail, and should not limit the scope of the present invention.
[0134] [Preparation Example: Preparation of Perovskite Oxide Thin Film]
[0135] (Example)
[0136] (Ba,Ca)TiO3 epitaxial films with A-site atomic layer gradient were grown on commercially available SrTiO3(001) single crystal substrates by pulsed laser deposition (PLD).
[0137] The SrTiO3 substrates were prepared by soaking in deionized water for 1 hour and etching with buffered hydrofluoric acid for 30 seconds.
[0138] Subsequently, the substrate was annealed in oxygen at 1000 °C for 6 h to produce an atomically smooth single TiO2 surface with unit cell steps.
[0139] Then, SrRuO3 layers each having a thickness of 20 nm and 5 nm were deposited as the lower electrode and the upper electrode, respectively.
[0140] Here, by using an energy density of 1.5 J / cm 2 The SrRuO3 thin film is deposited with a KrF excimer laser (λ=248 nm) of 3 Hz or less at a repetition rate.
[0141] During the growth process, the temperature and oxygen partial pressure were maintained at 675 °C and 100 mTorr, respectively.
[0142] In the PLD system, reflection high energy electron diffraction (RHEED) was installed to continuously monitor the growth rate.
[0143] Based on the RHEED vibration data of each BaTiO3 and CaTiO3 film grown on a 20nm thick SrRuO3 lower electrode, the (Ba,Ca)TiO3 film with A-site atomic layer gradient was controlled to have a deposition rate of 0.2μc / pulse or less ( Figure 2 ).
[0144] The (Ba,Ca)TiO3 thin films with A-site atomic layer gradient were grown under the following conditions: a temperature of 600°C and a laser energy density of 1.0 J / cm 2 or lower, oxygen partial pressure of 10mTorr, and repetition rate of 1Hz.
[0145] (Comparative Example)
[0146] BaTiO3 with a thickness of 1 μc and a solid solution BaTiO3 with a thickness of 1 μc were prepared under the same conditions as in Example 1. 0.5 Ca 0.5 TiO3 thin films and alternately grown superlattices BaTiO3 / CaTiO3.
[0147] After the growth process, the resulting film was slowly cooled to room temperature under 100 Torr oxygen.
[0148] In order to measure the frequency-dependent dielectric properties, a 60 nm thick Pt layer was deposited on top of the SrRuO 3 layer by electron beam deposition.
[0149] The upper Pt of the SrRuO3 electrode was patterned by electron beam lithography and ion milling and had a diameter size of 15 μm and a thickness of 70 nm or less.
[0150] In order to measure the thermoelectric properties according to the sinusoidal temperature change, a 20 nm thick SrRuO3 bottom electrode, a (Ba, Ca)TiO3 film with an A-site atomic layer gradient, a (Ca, Ba)TiO3 film with an atomic layer gradient in the opposite direction to that of the (Ba, Ca)TiO3 film, and a solid solution Ba 0.5 Ca 0.5 After the TiO3 film, a Pt electrode with a thickness of 60nm and a diameter of 50μm was formed by lift-off method.
[0151] [Experimental Example 1: Polarization characteristics of perovskite oxide thin films]
[0152] Figure 3 The solid solution Ba prepared in the comparative example is shown. 0.5 Ca 0.5 Aberration-corrected scanning transmission electron microscopy (STEM) measurements of TiO3 thin films, and Figure 4 The aberration-corrected scanning transmission electron microscopy (STEM) measurement results of the (Ba,Ca)TiO3 thin film with A-site atomic layer gradient prepared in Example are shown.
[0153] Reference Figure 3 and Figure 4 The high quality of the film and the atomic ratio gradient of the A-site atomic layer are confirmed by the gradual change in contrast, and are consistent with the solid solution Ba with uniform Ba and Ca atoms throughout the film. 0.5 Ca 0.5 Compared with the (Ba,Ca)TiO3 film, the (Ba,Ca)TiO3 film with A-site atomic layer gradient shows a gradual change in the number of Ba and Ca atoms.
[0154] Figure 5 The solid solution Ba prepared in the comparative example is shown. 0.5 Ca 0.5 Results of atomic-level chemical mapping of TiO3 films using energy dispersive X-ray spectroscopy (EDS), and Figure 6 Results of atomic-level chemical mapping using energy dispersive X-ray spectroscopy (EDS) of a (Ba,Ca)TiO 3 thin film with an A-site atomic layer gradient prepared in Example are shown.
[0155] Reference Figure 5 and Figure 6 , solid solution Ba 0.5 Ca 0.5 TiO3 films exhibit a uniform lattice without significant deviations, but (Ba,Ca)TiO3 films with an A-site atomic layer gradient show a clear gradient of lattice strain, where the out-of-plane lattice parameter decreases from BaTiO3 to CaTiO3 along the chemical gradient.
[0156] Figure 7 and Figure 8 Shown are the corresponding Figure 5 and Figure 6 Polarization diagram.
[0157] Reference Figure 7 and Figure 8 , solid solution Ba 0.5 Ca 0.5 The TiO3 film did not show obvious polarization, but the (Ba,Ca)TiO3 film with A-site atomic layer gradient produced an average of 28.4 μC cm -2 The large downward polarization, which locally reaches 60 μC cm near the bottom BaTiO3 layer, -2 .
[0158] [Experimental Example 2: Dielectric Properties of Perovskite Oxide Thin Films]
[0159] To measure the dielectric properties of (Ba,Ca)TiO3 thin films with A-site atomic layer gradient, a metal-insulator-metal structure was prepared. The structure consisted of a 60nm thick Pt layer and a 5nm thick SrRuO3 layer as the upper electrode.
[0160] Fig. 9 The solid solution Ba prepared in the comparative example is shown. 0.5 Ca 0.5 Graph showing the frequency-dependent dielectric constant of the (Ba,Ca)TiO3 film with A-site atomic layer gradient prepared in TiO3 film, etc. and Examples, Fig.10 The solid solution Ba prepared in the comparative example is shown. 0.5 Ca 0.5 Graph showing the tan δ characteristics of the (Ba,Ca)TiO3 thin film with A-site atomic layer gradient prepared in TiO3 thin films, etc. and Examples.
[0161] For comparison, BaTiO3 (BTO), solid solution Ba 0.5 Ca 0.5 TiO3(BCTO) and superlattice BaTiO3 / CaTiO3(BCTO).
[0162] Reference Fig. 9 and Fig.10 , (Ba,Ca)TiO3 thin films with A-site atomic layer gradient (atomic gradient BCTO) exhibit stable dielectric constant and low tanδ in the frequency range of 1kHz to 2MHz. Here, tanδ decreases and then increases according to frequency, which indicates that conduction and interface polarization losses occur at low frequencies, but relaxation polarization losses occur at high frequencies.
[0163] [Experimental Example 3: Thermoelectric properties of perovskite oxide thin films]
[0164] In order to measure the thermoelectric properties of (Ba,Ca)TiO3 thin films with A-site atomic layer gradient, a metal-insulator-metal structure was prepared. As the upper electrode, a (Ba,Ca)TiO3 thin film with A-site atomic layer gradient (atomic gradient BCTO), a (Ca,Ba)TiO3 thin film with A-site atomic layer gradient (atomic gradient CBTO) and a solid solution Ba 0.5 Ca 0.5 Pt with a thickness of 60 nm and a diameter of 50 μm was formed on the TiO3 film by lift-off method.
[0165] Fig.11 The (Ba, Ca) TiO3 film with an A-site atomic layer gradient prepared in the example and the (Ca, Ba) TiO3 film with an A-site atomic layer gradient prepared in the comparative example are shown. 0.5 Ca 0.5 Graph of the thermoelectric current of a TiO3 thin film based on a sinusoidal temperature change.
[0166] Reference Fig.11 , the (Ba,Ca)TiO3 film with an A-site atomic layer gradient and the (Ca,Ba)TiO3 film with an A-site atomic layer gradient generate thermoelectric currents proportional to the temperature change over time (dT / dt) under the conditions of a sinusoidal 30-second temperature change period and a temperature change magnitude of 7.5K. Here, the thermoelectric currents of the (Ba,Ca)TiO3 film with an A-site atomic layer gradient and the (Ca,Ba)TiO3 film with an A-site atomic layer gradient exhibit phases that are proportional to the temperature change over time (dT / dt) but in opposite directions to each other, indicating that since the films have polarizations in opposite directions to each other, the charges measured in the upper electrode have opposite polarities. In contrast, the solid solution Ba 0.5 Ca 0.5 The TiO3 film showed a result proportional to the temperature change, which was confirmed to be a non-pyroelectric current generated by defects such as space charges or oxygen vacancies, rather than a thermoelectric current caused by polarization.
[0167] In summary, in this exemplary embodiment, an A-site atomic layer gradient film was successfully designed by controlling the A-site atoms in the ATiO 3 perovskite structure.
[0168] The (Ba,Ca)TiO3 film with A-site atomic layer gradient shows that in a 11μc thick film, the atomic gradient induces a 20×10 6 / m strain gradient without structural defects.
[0169] As a result, the flexoelectric field generated 60 μC cm in the (Ba,Ca)TiO3 film with A-site atomic layer gradient. -2 Large local electric polarization.
[0170] (Ba,Ca)TiO3 thin films with A-site atomic layer gradients have a low-loss (e.g., tan δ less than 0.1) dielectric constant of about 220 in the frequency range of 1 kHz to 2 MHz, similar to that of 2D nanosheets.
[0171] In addition, the thermoelectric coefficients of the (Ba,Ca)TiO3 film with A-site atomic layer gradient and the (Ca,Ba)TiO3 film were measured to be about 2.55×10 6 μC / m 2 K.
[0172] While the present invention has been described in conjunction with what are presently considered to be practical example embodiments, it is to be understood that the invention is not limited to the disclosed embodiments, but is intended to cover various modifications and equivalent arrangements included within the spirit and scope of the appended claims.
[0173] <Description of Reference Numerals>
[0174] 100: Perovskite oxide thin films
[0175] AL1, AL2, AL3, AL4: first atomic layer, second atomic layer, third atomic layer, fourth atomic layer.
Claims
1. A perovskite oxide thin film comprising a compound represented by Chemical Formula 1 and having a layered perovskite structure, in, The ratio of A' atoms to all A sites in one A-site atomic layer is different from the ratio of A' atoms to all A sites in three or more other A-site atomic layers in the thickness direction: [Chemical Formula 1] A 1-x A' x BO3 Wherein, in Chemical Formula 1, A and A' are different divalent or trivalent cations, B is a tetravalent or trivalent cation, and 0≤x≤1。 2. The perovskite oxide thin film according to claim 1, wherein: A and A' each independently include Sr, Ca, Ba, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, or a combination thereof, and B includes Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, or a combination thereof.
3. The perovskite oxide thin film according to claim 1, wherein: Said one A-site atomic layer is the first atomic layer, and the first atomic layer is the A-site atomic layer located on the inner side in the thickness direction of the perovskite oxide film, and Said three or more different A-site atomic layers include: A second atomic layer, which is the A-site atomic layer located on one surface of the perovskite oxide film; A third atomic layer, which is the A-site atomic layer located on the other surface of the perovskite oxide film; and A fourth atomic layer, which is the A-site atomic layer located on the inner side in the thickness direction of the perovskite oxide film and different from the first atomic layer.
4. The perovskite oxide thin film according to claim 3, wherein: The ratio R of A' atoms to all A sites in the first atomic layer and the fourth atomic layer 1 are each independently greater than 0 and less than 1, The ratio R of A' atoms in the second atomic layer to all A sites 2 is greater than or equal to 0 and less than 1, and The ratio R of A' atoms to all A sites in the third atomic layer 3 Greater than 0 and less than or equal to 1.
5. The perovskite oxide thin film according to claim 3, wherein: Said first atomic layer is the A-site atomic layer of the compound represented by Chemical Formula 1, Said second atomic layer is the A-site atomic layer of the compound represented by Chemical Formula 2, Said third atomic layer is the A-site atomic layer of the compound represented by Chemical Formula 3, and Said fourth atomic layer is the A-site atomic layer of the compound represented by Chemical Formula 4, [Chemical Formula 2] ABO3 Wherein, in Chemical Formula 2, A is a divalent or trivalent cation different from A', and B is a tetravalent or trivalent cation, [Chemical Formula 3] A'BO3 Wherein, in Chemical Formula 3, A' is a divalent or trivalent cation different from A, and B is a tetravalent or trivalent cation, [Chemical Formula 4] A 1-z A' z BO3 Wherein, in Chemical Formula 4, A and A' are different divalent or trivalent cations, B is a tetravalent or trivalent cation, 0 < z < 1, and z ≠ x.
6. The perovskite oxide thin film according to claim 5, wherein: The compound represented by Chemical Formula 1 is Ba 1-x Ca x TiO3, The compound represented by Chemical Formula 2 is BaTiO3, The compound represented by Chemical Formula 3 is CaTiO3, and The compound represented by Chemical Formula 4 is Ba 1-z Ca z TiO3.
7. The perovskite oxide thin film according to claim 1, wherein: The perovskite oxide film has the following thickness direction gradient: the ratio of A' atoms to all A sites in one A-site atomic layer varies in the thickness direction.
8. The perovskite oxide thin film according to claim 7, wherein: The thickness direction gradient calculated by Equation 1 is 0.5% to 50%: [Equation 1] <h2 style=";text-align:left;direction:ltr">△G(%)=(AL<h2 style=";text-align:left;direction:ltr"> n+1 <h2 style=";text-align:left;direction:ltr"> -AL<h2 style=";text-align:left;direction:ltr"> n <h2 style=";text-align:left;direction:ltr"> )×100 Wherein, in Equation 1, △G is the gradient in the thickness direction, AL n is the ratio of A' atoms in any A-site atomic layer to all A-sites, and AL n+1 is the ratio of A' atoms in other A-site atomic layers with a spacing less than or equal to 0.4 nm to all A-sites.
9. The perovskite oxide thin film according to claim 1, wherein: The total thickness of the perovskite oxide film is 1.2 nm to 100 nm.
10. The perovskite oxide thin film according to claim 1, wherein: The atomic ratio of A atoms to A' atoms in the entire perovskite oxide film is 30:70 to 70:
30.
11. The perovskite oxide thin film according to claim 10, wherein: The average magnitude of the polarization induced throughout the perovskite oxide film is greater than or equal to 20 μC / cm 2 .
12. The perovskite oxide thin film according to claim 10, wherein: Under the measurement conditions of a frequency of 1 kHz to 2 MHz and an AC level of 10 mV to 200 mV, the dielectric loss of the entire perovskite oxide film is less than or equal to 0.
1.
13. The perovskite oxide thin film according to claim 10, wherein: Under the measurement conditions of a sinusoidal temperature change cycle of 20 seconds to 120 seconds and a temperature change of 0.5K to 8K, the thermoelectric coefficient of the entire perovskite oxide film is greater than or equal to 10 5 μC / m 2 K.
14. A method for preparing a perovskite oxide film, comprising: forming a perovskite oxide thin film on a substrate, the perovskite oxide thin film including a compound represented by Chemical Formula 1 and having a layered perovskite structure, where the ratio of A' atoms in one A-site atomic layer to all A-sites is different from the ratio of A' atoms in three or more other A-site atomic layers to all A-sites in the thickness direction: [Chemical formula 1] A 1-x A' x BO3 Wherein, in Chemical Formula 1, A and A' are different divalent or trivalent cations, B is a tetravalent or trivalent cation, and 0≤x≤1。 15. The method according to claim 14, wherein: The perovskite oxide film is formed by: Physical vapor deposition, chemical vapor deposition, molecular beam epitaxy, atomic layer deposition or pulsed laser deposition.
16. The method according to claim 14, wherein: The perovskite oxide thin film is formed using a pulsed laser deposition device equipped with a high-pressure and high-speed reflection electron diffraction device under specific conditions of a rate of 2 pulses / unit cell to 200 pulses / unit cell.
Citation Information
Patent Citations
Augmented reality content generator for destination activities
KR1020230076849A
